Microwave radiation associated with stepped leaders of negative cloud-to-ground flashes - Baharin S.A.S.; Ahmad M.R.; Al-Shaikhli T.R.K.; Sidik M.A.B.; Sabri M.H.M.; Al-Kahtani A.A.N.; Mohammad S.A.; Lu G.; Zhang H.; Cooray V. (Elsevier Ltd, 2023)
Bandwidth; Clouds; Electrons; Microwave antennas; Microwave sensors; Cloud-to-ground flash; Electron avalanches; Head-on collision; High-frequency radiation; Leadtime; Microwave pulse; Radiation pulse; Stepped leader; Streamer; Very high frequency; Microwaves; cloud to ground lightning; corona; electron; microwave radiation